Gender differences in the effect of social support on health-related quality of life: results of a population-based prospective cohort study in old age in Germany - Hajek, André; Weyerer, Siegfried (Quality of life research, 2016)
Purpose: The causality between social predictors and HRQoL in old age remains almost unclear as only a few studies have examined the influence of social support on HRQoL in a longitudinal setting. Moreover, available studies investigating gender differences in the effect of social support on HRQoL in old age have been solely cross-sectional. Consequently, the aim of this study was to examine whether social support affects health-related quality of life (HRQoL) in old age and whether this effect is moderated by gender. Methods: In a population-based cohort (N = 2443) of people aged 75 years and older in Germany, the development of HRQoL was prospectively observed over a 3-year period. Quality of life was quantified by using the visual analogue scale of the EQ-5D instrument. Social support was assessed by using the 14-item form of the questionnaire for social support (F-SozU K-14). In order to control for unobserved heterogeneity, fixed-effects regression analysis was used. Results: In the total sample (β = 0.55, p < 0.05) and in men (β = 1.39, p < 0.001), a strong positive impact of social support on HRQoL was found. There was no significant effect of social support on HRQoL in women. The effect of social support on HRQoL was significantly moderated by gender (p < 0.05). Conclusions: Findings accentuate the fundamental role of social support in HRQoL in old age. Particularly in men, it is therefore crucial to strengthen the social ties in old age.
Gesehen am 06.05.2019
Published online: 27 October 2015